Thiruppugazh –Worship Through Chandam - Suhanya, A. (Pranav Journal, 2021)
Hindu culture at its core is very much religious and spiritual. So the Hindu traditional music is also spiritual, in its own way. Playing classical music is like meditation: it is not only meant to entertain, but to take us to a higher domain of consciousness. The very structure of Indian classical music is spiritual. It lifts the spirit; it is for the soul. Indian music can also be a medium to self-realization. History of Tamil Thevara Mum moorthikal shows us the power of the worship through music. Pray the load by sung Thevaara Thirumuraikal got the spring of the divine blessings. Especially the Thiruppugazh hymns presented by Arunagirinaathar are that it is based entirely on a metrical pattern which varies from song to song. This pattern is called as „Chandam‟ and Arunagirinathar came to be called as the „Chanda Paavala Peruman‟, the one well versed in candam poetry. The Hindu intellectuals gave a special place for the Thiruppugazh according to the specialty of musical aspects. Thiruppugazh is the best hymns for the worship through music. Hence, this article deals with the power of the musical worship and the special musical aspects of Thiruppugazh.
Keywords: Thiruppugazh; Arunagirinaathar; Carnatic Music; Chandam; Naama sangeerthana